In silico high-throughput screening system for AKT1 activators with therapeutic applications in sepsis acute lung injury - Wang, Ziyi; Wang, Xuesong; Guo, Zhe; Liao, Haiyan; Chai, Yan; Wang, Ziwen; Wang, Zhong (Frontiers in Cellular and Infection Microbiology, 2022)
Purpose: AKT1 is an important target in sepsis acute lung injury (SALI). The current study was aim to construct a high-throughput screening (HTS) system based on the ChemDiv database (https://www.chemdiv.com/complete-list/) and use the system to screen for AKT1 activation agents, which may provide clues for the research and development of new drugs to treat SALI. Methods:Based on the existing X-ray structure of AKT1 and known AKT activators, a large-scale virtual HTS was performed on the ChemDiv database of small molecules by the cascade docking method and demonstrated both accuracy and screening efficiency. Molecular docking and molecular dynamics simulations were used to assess the stability and binding characteristics of the identified small-molecule compounds. The effects of selected SALI activators on SALI were verified by in vitro and in vivo experiments. Results: The small-molecule compound 7460-0250 was screened out as a specific activator of AKT1. Molecular validation experiments confirmed that compound 7460-0250 specifically promoted the phosphorylation of AKT1 and downregulated the LPS-induced apoptosis of human umbilical vein endothelial cells (HUVECs) by activating the AKT-mTOR pathway. Up-regulated mTOR was detected to directly interact with Bax to reduce apoptosis. In vivo, compound 7460-0250 could improved survival rate and alleviated lung injury of SALI mice induced by cecum ligation and puncture (CLP). Conclusion: small-molecule compound 7460-0250 was successfully screened and confirmed as a specific AKT1 activator, which is a critical target in the development of new therapeutics for SALI.